2021
DOI: 10.1016/j.jsps.2021.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Work readiness scale for pharmacy interns and graduates: A cross-sectional study

Abstract: Introduction As the number of unemployment among pharmacy graduates increases, the Saudi Ministry of Labor implemented extra measures to facilitate their training and hiring by the private sectors. Nevertheless, there is a paucity of data regarding pharmacy graduates’ work readiness (WR). Hence, we aim to assess their WR and identify predicting factors associated with WR among pharmacy graduates’ in Saudi Arabia. Methods A 46-item self-reported pre-validated anonymous w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Furthermore, another study in Australia found that work competence and organizational acumen scores were higher than those reported in this study (Dudley et al, 2020). Interestingly, the high scores in all dimensions reported by newly graduated nurses in this study were comparable to those reported among freshly graduated pharmacists and pharmacy interns in Saudi Arabia (Almarzoky Abuhussain et al, 2021). However, compared to a study in the United States (Walters et al, 2022), Saudi graduate nurses had lower scores in overall work readiness and social intelligence, personal work characteristics and organizational acumen dimensions.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, another study in Australia found that work competence and organizational acumen scores were higher than those reported in this study (Dudley et al, 2020). Interestingly, the high scores in all dimensions reported by newly graduated nurses in this study were comparable to those reported among freshly graduated pharmacists and pharmacy interns in Saudi Arabia (Almarzoky Abuhussain et al, 2021). However, compared to a study in the United States (Walters et al, 2022), Saudi graduate nurses had lower scores in overall work readiness and social intelligence, personal work characteristics and organizational acumen dimensions.…”
Section: Discussionsupporting
confidence: 83%
“…Internship is a critical period for most graduates' career decision-making, and graduation internship is an important way for students to fully understand the content of the work and the current situation of employment, so that they can better choose employment and further education reasonably according to their actual situation, In addition, internship can provide better preparation for future clinical work. Therefore, during the internship period, we should enhance the interns' awareness of the pharmacy profession and their career planning for the future [33,34] . The core competencies of hospital pharmacists refer to the knowledge, skills, judgment, and personal attributes required for pharmacists to provide safe, effective, cost-effective, and ethical patientcentered pharmacy services, including professional practice, coordination and communication, management, professional development, and critical thinking [35][36][37] .…”
Section: Discussionmentioning
confidence: 99%
“…Examples of items include: "I have a solid theoretical understanding of my field of work", "I can't wait to start work and throw myself into a project", and "I am eager to throw myself into my work" Each item is rated on 5-point Likert scale, with higher scores indicating higher levels of career readiness. The scale has been found to have good reliability and validity for the assessment of career readiness in pharmacy graduates and interns (Almarzoky Abuhussain et al, 2021).…”
Section: Career Readinessmentioning
confidence: 98%